Seashells - Cleave, Andrew (Creatures of the ocean., 2020)
Presents an illustrated look at seashells around the world, discussing shell structure, classifications, locations, and the ethics of shell collecting. Includes dozens of color photographs, further reading, internet resources, and QR codes that link to educational videos.